Initial experience of cardiac catheterization through distal radial access in a femoralist center - Alfonso Rodriguez, Emilio; Llerena Rojas, Lorenzo; López Ferrero, Leonardo; Zabala García, Aresky; Lopez Cabrera, Giselle (Revista Cubana de Investigaciones Biomédicas, 2020)
Objective: to share our experience in the radial distal approach to perform coronary angiography and / or dilation of coronary stenosis. The initial results are exposed in the access of the distal radial artery or in the so-called anatomical "tobacco". Methods: The left or right radial distal artery was used as an access site in 6 patients admitted to the Institute of Cardiology and Cardiovascular Surgery for coronary angiography and dilatation of coronary stenosis between May 6 and June 6 of 2019. All with pulse present in their distal radial artery. In the laboratory, they had the access arm flexed with respect to the homolateral shoulder so that the hand was placed on their contralateral groin. In all cases, the operator was placed on the right side of the patient, to perform coronary angiography and / or dilation of coronary stenosis. During the hospital stay, the main demographic characteristics and complications were recorded. Results: the average age of the patients was 72 +/- 10 years and 83.3% were men. We use the Judkins and Amplatz 6 and 5 French catheters for the procedures. Five admitted with the diagnosis of angina and one with severe aortic valve stenosis. In 5 patients, distal transradial coronary angiography was successfully performed. Only one patient experienced distal radial spasm, using in this case the ipsilateral proximal radial access, without making it necessary to approach the femoral artery. In total, 4 patients had coronary intervention, performing successfully in the 4 patients. The right coronary artery was the artery that required most of the intervention (3 patients). There were no cases of occlusion of the radial arteries, no hematoma of the hand, of the B.A.R.C scale greater than 1 was observed in any patient. Numbness of the hand was documented in none. The radial introducer was removed at the end of the procedure. Hemostasis was achieved with manual compression. Conclusion: the distal radial approach is feasible in a selected group of patients as a procedure for coronary angiography and dilatation of coronary stenosis.